Sustainability and discounted utilitarianism in models of economic growth - Geir B. Asheim; Tapan Mitra (Center for Economic Studies and ifo Institute (CESifo), 2009)
Discounted utilitarianism treats generations unequally and leads to seemingly unappealing consequences in some models of economic growth. Instead, this paper presents and applies sustainable discounted utilitarianism (SDU). SDU respects the interests of future generations and resolves intergenerational conflicts by imposing on discounted utilitarianism that the evaluation be insensitive to the interests of the present generation if the present is better off than the future. An SDU social welfare function always exists. We provide a convenient sufficient condition to identify SDU optima and apply SDU to two well-known models of economic growth. We also investigate the axiomatic basis for SDU.
Keywords: D63; D71; Q01; 330; Intergenerational equity; sustainability; discounted utilitarianism; egalitarian consumption streams; efficiency; exhaustible resources; Zeitpräferenz; Soziale Diskontrate; Nachhaltige Entwicklung; Generationenbeziehungen; Gerechtigkeit; Theorie